PENINGKATAN KAPASITAS PRODUKSI KACANG METE MELALUI PERBAIKAN PERALATAN PRODUKSI DAN LINGKUNGAN KERJA - Sutrisno Sutrisno; Mohamad Endy Yulianto; Didik Ariwibowo (Sekolah Vokasi Universitas Diponegoro, 2023)
Market driven increasing of fried and roasted cashew nut leads UD. Tiga Saudara to increase its capacity. Improvement of production equipments is one of the effort. Therefore IDBU programme aims to increase the capacity by modification of tray-type-oven, oil-drain spinner, and faster packing machine/sealer. A comprehensive steps is needed to achieve the IDBU programme target, those are: (i) design and fabrication of 20 kg/batch tray-type-oven with ON/OFF temperature control, (ii) design and fabrication of 7,5 kg/batch spinner, (iii) design and fabrication of 200 pack/hour conveyor-sealer, and (iv) realability of the machine. Implementation result of this programme are able to increase the processing capacity of cashew nuts up to 50%